DERAJAT INFEKSI MIKORIZA PADA PERSIAPAN LAHAN DAN PENGELOLAAN GULMA DI TIGA KABUPATEN DI PROVINSI SUMATERA UTARA - F Fitria; Fitra Syawal Harahap; Hilwa Walida (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
This study was aimed to elucidate the level of degree of mycorrhiza infection with some way of land preparation and weed management in Deli Serdang, Karo and Simalungun Regencies of North Sumatera Province. The percentage of degrees of mycorrhiza infection in maize roots was observed in the laboratory at the end of the vegetative period using a magnification microscope of 100 times. It was carried out by choosing a fine root (root hair) from a representative of various sides of the roots with a diameter of between 0.2 and 2 mm, washed with clean running water then put the root into 10% KOH solution and left for 24 hours. Results of the study indicated that the best treatment of soil treatment and weed control was 32.67% in T3 treatment (OTS 21 and 42 HST weeded) and the lowest was 11.00% in T6 treatment (TOT 21 and 42 HST paraquat application) and had a significant effect on Karo Regency with the best value of 31.33% T1 (OTS 21 and 42 HST paraquat applications) and the lowest value of 10.00% in T10 treatment (TOT and no controlled weeds). Soil treatment with twice weedings caused the highest degree of mycorrhiza infection in Deli Serdang Regency, while soil treatment with twice application of paraquat resulted in the highest degree of mycorrhiza infection in Karo Regency.